El catastro municipal y su incidencia en la recaudacion tributaria de los ingresos fiscales del gobierno autonomo descentralizado del canton Quevedo, periodo 2014-2015. - Muñoz Solórzano, Jennifer María (2016)
The present research on "The municipal land and its impact on tax collection of tax revenue of the Autonomous Decentralized Government Quevedo Canton, period 2014-2015". It aims to determine the cadastral system in generating financial resources for municipal development plan of the Autonomous Government Decentralized City Quevedo. Therefore the research is based on the conceptual and referential framework for the cadastral system, financial resources, municipal land administration, land tax collection, updating land records, rules or laws, so that the study of these variables of inquiry are necessary to expand knowledge and learn about the municipal taxation. The administration Decentralized Autonomous Municipal Government Quevedo canton is implementing a number of changes in their functional areas, but the cadastral system must make more efficient on the valuation of the properties, with a percentage of 35% of respondents state that the collection tax not resolve public works for citizenship. The municipal development plan promoted by the municipal council must be balanced starting with the most essential needs for the good life of the inhabitants of the canton Quevedo, for this reason the competent authorities of a better administration of the area of land to be asked people are satisfied with the value of their land and come to the municipal coffers to pay their taxes, higher revenues running to generate works and welfare programs. Keywords: municipal cadastre, tax collection, tax revenue, Government Autonomous Decentralized.